FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study aims to examine the factors that affect the profitability of banking companies listed in Indonesia Stock Exchange Consist of capital adequacy ratio, Loan to Deposit Ratio, Loans, Operational Efficiency, Non Performing Loans, and Third Party Funds. The population in this study are all banking companies listed on the Indonesia Stock Exchange from 2009 to 2012. While the sample is determined by purposive sampling method in order to obtain 25 sample firms. This hypothesis was tested using Multiple Llinear Analysis. Based on the test results shown that to Deposit Ratio and Third Party Funds has a positive effect on Return on Assets. While the capital adequacy ratio, Loans, Operational Efficiency, and Non-Performing Loans negative  affect the Return on Assets.Keywords: Capital Adequacy Ratio, Loan to Deposit Ratio , Loans, Operational Efficiency, Non-Performing Loans, Third Party Funds, Return on Assets.